2016
DOI: 10.1111/jep.12613
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐to‐delivery interval in pregnant women with intrapartum non‐reassuring fetal heart rate patterns

Abstract: Only 6.6% of women with non-reassuring FHR achieved the 30-minute goal for caesarean delivery (median 56 minutes). Better performance was observed among patients in FHR category 3 regardless of diagnosis time, with 41.2% of these patients having a DDI of <30 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
2
10
1
Order By: Relevance
“…Previous studies reported an improvement in the time to delivery by implementing a multidisciplinary protocol, a team training with more effective communication and an obstetric care process [ 19 20 ]. The results of this study also showed some improvement in the care process among women with non-reassuring FHR, compared to a recent report from the same institution [ 14 ]. Achievement of 30-minute goal increased from 6.6% to 18.8% and rate of delivery in ≤75 minutes increased from 69.5% to 75%.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies reported an improvement in the time to delivery by implementing a multidisciplinary protocol, a team training with more effective communication and an obstetric care process [ 19 20 ]. The results of this study also showed some improvement in the care process among women with non-reassuring FHR, compared to a recent report from the same institution [ 14 ]. Achievement of 30-minute goal increased from 6.6% to 18.8% and rate of delivery in ≤75 minutes increased from 69.5% to 75%.…”
Section: Discussionsupporting
confidence: 62%
“…In Thailand, there is limited information regarding the time interval for emergency cesarean delivery and no specific recommendation has been adopted. A recent report in Thailand showed that only 6.6% of women with non-reassuring fetal heart rate (FHR) pattern achieved the 30-minute goal for cesarean delivery with a median time of 56 minutes [ 14 ]. However, such study focused on only women with non-reassuring FHR, but not on women with other indications for emergency cesarean delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal outcomes were comparable irrespective of DDI. 21 Our data suggest formal inclusion of MOFR into EFM interpretation (FRI) seems to allow for earlier and more accurate prediction of fetal intolerance to labor requiring EOD when compared to currently utilized interpretation and management methodology. In an earlier study, we found that ACOG category III appears too far to the right on the curve to be helpful for either timely identifying or preventing serious fetal injury or EOD.…”
Section: Discussionmentioning
confidence: 79%
“…Neonatal outcomes were comparable irrespective of DDI. 21…”
Section: Discussionmentioning
confidence: 99%
“…Yakasai et al, 15 found that despite a delay of > 30min in 87% cases, about 83.4 % of the cases had a good fetomaternal outcome. Boriboonhirunsarn et al, 16 found a DDI of >3 0 min for Category 1 CS in 93.4% of cases and noted no significant difference among groups relative to birth weight, birth asphyxia and NICU admission.…”
Section: Discussionmentioning
confidence: 94%